FRPR-4 Is a G-Protein Coupled Neuropeptide Receptor That Regulates Behavioral Quiescence and Posture in Caenorhabditis elegans - Nelson, Matthew D.; Janssen, Tom; York, Neil; Lee, Kun He; Schoofs, Liliane; Raizen, David M. (PLOS ONE, 2015)
Neuropeptides signal through G-protein coupled receptors (GPCRs) to regulate a broad array of animal behaviors and physiological processes. The Caenorhabditis elegans genome encodes approximately 100 predicted neuropeptide receptor GPCRs, but in vivo roles for only a few have been identified. We describe here a role for the GPCR FRPR-4 in the regulation of behavioral quiescence and locomotive posture. FRPR-4 is activated in cell culture by several neuropeptides with an amidated isoleucine-arginine-phenylalanine (IRF) motif or an amidated valine-arginine-phenylalanine (VRF) motif at their carboxy termini, including those encoded by the gene flp-13. Loss of frpr-4 function results in a minor feeding quiescence defect after heat-induced cellular stress. Overexpression of frpr-4 induces quiescence of locomotion and feeding as well as an exaggerated body bend posture. The exaggerated body bend posture requires the gene flp-13. While frpr-4 is expressed broadly, selective overexpression of frpr-4 in the proprioceptive DVA neurons results in exaggerated body bends that require flp-13 in the ALA neuron. Our results suggest that FLP-13 and other neuropeptides signal through FRPR-4 and other receptors to regulate locomotion posture and behavioral quiescence.